Bai li yan jiu - Zeng, Yi 1969- (Shanghai gu ji chu ban she, 2019)
Abstract
Keywords: Geschichte; Rites and ceremonies / China / History; Etiquette / China / History; Etiquette; Manners and customs; Rites and ceremonies; Brauch; Gesellschaftsleben; China / Social life and customs; China